2012
DOI: 10.3138/ptc.2011-06bh
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation in Patients with Dementia Following Hip Fracture: A Systematic Review

Abstract: Purpose: Best rehabilitation practices after hip fracture for people with dementia have not been established. A systematic review was conducted to determine current evidence for rehabilitation in this population, including residents in continuing care. Methods: Standardized review methodology was used to search eight databases for literature on hip-fracture rehabilitation for people with dementia. Eligible studies included participants with dementia who had a hip fracture; performed a rehabilitation interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 44 publications
(50 reference statements)
3
58
0
2
Order By: Relevance
“…It also addressed some of the gaps in hip fracture rehabilitation, such as the lack of interventions that enhance self-efficacy 24,169,242,243 and address postural balance and fear of falling, 14,21,24,169 the exclusion of moderately cognitively impaired patients, 10,16,17,24,36,57,244 the short-term provision of rehabilitation services 10,244 and the lack of reporting of carer outcomes. 10 Self-efficacy to exercise has long been recognised as an important mediator for regaining confidence in daily activities and function and overcoming the fear of falling, to enable an increase in the practice of physical activities and exercise.…”
Section: Comparison With Previous Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…It also addressed some of the gaps in hip fracture rehabilitation, such as the lack of interventions that enhance self-efficacy 24,169,242,243 and address postural balance and fear of falling, 14,21,24,169 the exclusion of moderately cognitively impaired patients, 10,16,17,24,36,57,244 the short-term provision of rehabilitation services 10,244 and the lack of reporting of carer outcomes. 10 Self-efficacy to exercise has long been recognised as an important mediator for regaining confidence in daily activities and function and overcoming the fear of falling, to enable an increase in the practice of physical activities and exercise.…”
Section: Comparison With Previous Literaturementioning
confidence: 99%
“…7 However, a systematic review of rehabilitation in patients with dementia following hip fracture found that those with mild to moderate dementia showed similar relative gains in function to those without dementia. 17 In addition, hip fracture patients with cognitive impairment are at increased risk of delirium, medical complications, death, prolonged stay and loss of independence. According to the NICE guidelines on delirium, 18 patients with memory problems are known to benefit from comprehensive geriatric assessment and targeted intervention to reduce the risk of delirium.…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…198,199 Rehabilitation programs have been shown to be effective in the patient with dementia although the best approach is currently unknown. 200 The length and intensity of rehabilitation after hip fracture is a topic of great importance. Studies have shown that long periods of rehabilitation improve function.…”
Section: Rehabilitationmentioning
confidence: 99%
“…6 Recent studies provide conflicting evidence regarding the factors that influence recovery in older adults with hip fracture after discharge from inpatient rehabilitation. Factors such as prefracture cognitive and functional status, 7,8 cognitive impairment, [9][10][11][12][13][14][15][16] age, 17 sex, [18][19][20] medical co morbidities, 21 and pain 22 have been found to influence recovery, function, and mobility outcomes over time in older adults after hip fracture, 12,[14][15][16] yet two systematic reviews indicated that individuals with cognitive impairment made gains that were similar to those of individuals without cognitive impairment. 16,23 Albeit informative, these studies were unclear as to how many individuals with complex needs were offered active rehabilitation, the type and approaches used during rehabilitation, and the extent to which inpatient care influenced long-term outcomes.…”
mentioning
confidence: 99%